2017
DOI: 10.5858/arpa.2017-0055-oa
|View full text |Cite
|
Sign up to set email alerts
|

Telepathology at the Armed Forces Institute of Pathology: A Retrospective Review of Consultations From 1996 to 1997

Abstract: - Using commercial off-the-shelf technology and despite telecommunication challenges during that time, the AFIP demonstrated that telepathology could be conducted reliably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…4,5 Dynamic telepathology enables pathologists to examine whole histological sections or cytological smears over any distance. 68 The promising application of these approaches in countries with restricted resources is well documented. 9,10 “Hybrid telepathology” combines video consultations and store-and-forward communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Dynamic telepathology enables pathologists to examine whole histological sections or cytological smears over any distance. 68 The promising application of these approaches in countries with restricted resources is well documented. 9,10 “Hybrid telepathology” combines video consultations and store-and-forward communication.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 “Hybrid telepathology” combines video consultations and store-and-forward communication. 10,11 On the whole, telepathology, including teleteaching, 713 is a promising method to connect the knowledge of consultant pathologists with the requirements of a physician in an underserved country.…”
Section: Introductionmentioning
confidence: 99%
“…WSI, captured on slide scanners, can be stored, organized, annotated, and transmitted digitally, even to remote areas. The contribution of telepathology is especially relevant in remote locations that lack specialists and/or access to advanced testing methods (eg, special stains, IHC) [28], and provides opportunities for pathologists to participate in collaborative review of cases and research over distances. While several studies have demonstrated the utility of telepathology using WSI as an effective diagnostic modality in surgical pathology, mostly for neoplastic diseases, only rare studies have evaluated its utility for infectious disease diagnoses [27,[29][30][31][32].…”
Section: Telepathology: Virtual Discussion To Achieve Consensus Diagmentioning
confidence: 99%
“…Remote intraoperative consultation was one of the first use cases for digital pathology and arguably one of the most widely cited reasons for the adoption of WSI. 42 This allows for pathologists to be located in a centralized location in order to support peripheral sites (subject of course to licensing requirements), for example, in subspecialized signout, where intraoperative consultations are exclusively performed by subspecialized pathologists. 43,44 Remote consultation for routine cases is an additional use case that has been demonstrated in a few specific scenarios.…”
Section: Remote Consultation and Telepathologymentioning
confidence: 99%